Malignant Eccrine Porocarcinoma in Finland During 2007 to 2017 - Anna-Stiina Meriläinen; Eero Pukkala; Tom Böhling; Virve Koljonen (Acta Dermato-Venereologica, 2021)

(untitled)
Malignant eccrine porocarcinoma is a rare skin adnexal cancer arising from the sweat glands. Little is known about the epidemiology and incidence of eccrine porocarcinoma. This registry-based study examined the epidemiology and incidence data for eccrine porocarcinoma from the Finnish Cancer Registry. The study included all persons diagnosed with eccrine porocarcinoma in 2007 to 2017. There were 69 cases in the study period; 34 (49%) male and 35 (51%) female patients. Mean age at diagnosis was 75.5 years. Incidence for men was 0.06 per 100,000 person-years and for women 0.04 per 100,000 person-years adjusted for age according to the World Standard Population. Incidence increased with age. There was one eccrine porocarcinoma-specific death among the 69 patients. The incidence of eccrine porocarcinoma in Finland is therefore low. The mean age at time of diagnosis and the location of eccrine porocarcinoma are consistent with previous reports. The survival of patients with eccrine porocarcinoma is high.